Relationship Plasma Concentration of Zonulin with Severity Level of Autism Based on Criteria of Diagnostic and Statistical Manual of Mental Disorders-5 (Dsm-5) - Nanik Setijowati (Journal of Global Pharma Technology, 2019)
Background: This study was aimed to prove whether there is relationship between plasma concentration of zonulin and severity level of autism based on criteria of diagnostic and statistical manual of mental disorders-5 (DSM-5). In Indonesia, this kind of research has never been done, considering the incidence of autism is also increasing. Methods: The participants of this research were 38 autistic (level 1=17, level 2=12 and level 3= 9) and 35 control children. The blood plasma of all participants was taken to determine the plasma concentration of zonulin. The observation sheet was based on the DSM-5 as an instrument to determine the diagnosis of autistic children. Data were analyzed using Mann-Whitney and Anova test. Results: There was a significant difference plasma concentration of zonulin between autism and control (p = 0.002) with 32 ± 18 vs 47 ± 22.5, respectively. There was slightly different between plasma concentration of zonulin and severity level of autisme (p=0.239) with 32±19, 27±18, 40±15, respectively. Cut-off point 8 ng/mL (Sensitivity 97.4%, Spesificity 2.9%). Conclusion: This finding can be concluded that plasma concentrations  of zonulin were slightly related with severity, and the highest is at level 3.